Comparative Efficacy of Amiodarone and Lidocaine in Treating Cardiac Arrest Due to Ventricular Fibrillation and Pulseless Ventricular Tachycardia in Adults. A Literature Review - Dryja, Patryk; Boczar, Agata; Orzołek, Izabela; Stawicka, Izabela; Jarmołowicz, Jakub; Solisch, Sven; Solisch, Bianka (Journal of Education, Health and Sport, 2024)
Introduction:Sudden cardiac arrest (SCA) is a critical emergency, with shockable rhythms like ventricular fibrillation (VF) and pulseless ventricular tachycardia (VT) posing challenges. Amiodarone and lidocaine are key antiarrhythmic drugs used with defibrillation. While both improve hospital admission rates, their effects on survival and neurological outcomes remain unclear. This review examines their comparative efficacy to guide clinical practice. Materials and methods:A thorough literature review was performed using electronic databases. The search was restricted to English-language articles published from 1970 to 2024. Aim of the study:The aim of this study is to systematically review and compare the efficacy of lidocaine and amiodarone in the treatment of cardiac arrest due to ventricular fibrillation and ventricular tachycardia in adults. This review seeks to evaluate the existing literature to determine the effectiveness and clinical outcomes associated with each medication. Conclusions: The comparative analysis of amiodarone and lidocaine highlights their respective strengths and limitations in managing cardiac arrest, offering valuable insights for clinical practice. Amiodarone stands out as the preferred antiarrhythmic agent due to its significant efficacy in improving short-term outcomes, such as return of spontaneous circulation (ROSC) and survival to hospital admission. Overall, amiodarone’s efficacy and broader applicability position it as the first-line agent for shock-refractory ventricular fibrillation (VF) and pulseless ventricular tachycardia (pVT). Lidocaine serves as an important alternative in specific scenarios. Future research should aim to optimize antiarrhythmic protocols, improve long-term survival and neurological outcomes, and explore innovative approaches to resuscitation.